Strategy Building and Sustaining Competitive Advantage: A Case Study of Shangri-La Hotels (Malaysia) Berhad - Abdullah, Haim Hilman (2015)
This case study focuses on the best strategic initiatives of Shangri-La hotels (Malaysia) Berhad (SHMB) in strategy building and sustaining competitive advantage.It presently owns nine branches, namely Shangri-La's Rasa Ria Resort, Kota Kinabalu, Shangri-La's Tanjung Aru Resort and Spa, Kota Kinabalu, Putrajaya Shangri-La, Shangri-La Hotel, Kuala Lumpur, Traders Hotel, Kuala Lumpur, Traders Hotel, Puteri Harbour, Johor, Malaysia, Golden Sands Resort, Penang, Shangri-La's Rasa Sayang Resort & Spa, Penang and Hotel Jen Penang (Formerly Traders Hotel, Penang).The group is engaged in the ownership and operation of hotels and beach resorts, a golf course, investment properties and a commercial laundry. Hotel business represents a critical part of the tourism sector, which plays a pivotal role in driving the nation’s economic transformation agenda.Therefore, the Malaysian government is constantly implementing various policies and agendas to uphold the industry’s competitiveness and profitability growth. Although, the concerted efforts are underway, but some hoteliers are still facing several challenges in today’s highly competitive and rapidly evolving market.Hence, why certain hotels succeed in a dynamic competitive environment while rest fail? The answer might be simple and straightforward, but it is not easy.Hotels that grow and change are hotels that know how to build resilient strategies that secure and sustain competitive advantage.The notion of strategy building and sustaining competitive advantage are at the very heart of business success.In view of that, this case study mainly intends to analyse a case of successful SHMB from a strategic management perspective.There is an urgent need to look into the true competencies of SHMB in overcoming the challenges in the 21st century based on the right strategy formulation, implementation, evaluation, direction and decision making process and recognize their efforts to attain high income nation in 2020 as well as continuing to grow in the industry it now dominates.